HUBUNGAN ANTARA KARAKTERISTIK SPERMA DALAM MANI BEKU DENGAN KEBERHASILAN INSEMINASI BUATAN PADA SAPI PERAH FRISSIAN HOLSTEIN - Ahmad Taofik (JURNAL ISTEK, 2012)
The objective of this research was to evaluate of the relationship between sperm characteristics of frozen semen to artificial insemination results. The measurement of artificial insemination results were non return rate (NR) and conception rate (CR). The measurement of sperm characteristics were progressive motility, sperm membrane intact and acrosome intact. The correlation of sperm progressive motility, sperm membrane plasm intact and sperm acrosome intact to NR were 0,198, 0,216 and 0,968 respectively. The correlation of sperm progressive motility, sperm membrane plasm intact and sperm acrosome intact to CR were 0,100, 0,194 and 0,917 respectively. Based on all data, the sperm acrosome intact was high correlation to artificial insemination results.